Financial management - Titman, Sheridan 1954-; Keown, Arthur J.; Martin, John D. 1945- (Pearson, 2021)
This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. For undergraduate courses in corporate finance and financial management
Keywords: Finanzmanagement